2017
DOI: 10.1016/j.amjcard.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Industrial Compensation to Cardiologists in 2015

Abstract: The categorization and characterization of pharmaceutical and device manufacturers or group purchasing organization payments to clinicians is an important step toward assessing conflicts of interest and the potential impact of these payments on practice patterns. Payments have not previously been compared among the subspecialties of cardiology. This is a retrospective analysis of the Open Payments database, including all installments and payments made to doctors in the calendar year 2015 by pharmaceutical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…inequality among the physicians who received payments from the industry. The same trend has been noted in other studies analyzing industry payments to cardiologists and neurologists [5][6][7][8][9][10]. The trend of payments in the top 10 physicians was not much different from the total cohort; compensation for services (41.3%) and royalty and/or licensing fees (31.6%) were the most paid categories.…”
Section: Categories Of Paymentssupporting
confidence: 81%
“…inequality among the physicians who received payments from the industry. The same trend has been noted in other studies analyzing industry payments to cardiologists and neurologists [5][6][7][8][9][10]. The trend of payments in the top 10 physicians was not much different from the total cohort; compensation for services (41.3%) and royalty and/or licensing fees (31.6%) were the most paid categories.…”
Section: Categories Of Paymentssupporting
confidence: 81%
“…The characteristics of physicians who receive large payments from industry remain incompletely characterised. Several studies have reported that industry payments may vary substantially based on physicians’ sex,14–17 clinical experience16 18 and specialty 10 15 19 20. In addition, a recent study that reported association of physicians’ alma mater, medical school ranking and their prescription patterns (for opioids), sheds light on the importance of medical education on physician behaviour, which could potentially impact how industry approach physicians 21.…”
Section: Introductionmentioning
confidence: 99%
“…The data collection was started in 2013 and first reported in 2014. Recent studies on Open Payments have shown the significant financial interaction between the medical industry and physicians in various specialties 8‐16 . This also brought to light the inaccuracies of financial disclosure statements and conflicts of interests, thus advocating for more stringent enforcement of disclosure policies 6,17,18 .…”
Section: Introductionmentioning
confidence: 99%